Research on accuracy enhancement methods for highway slope deformation monitoring based on the BeiDou system - Yuhong Luo; Geyu Chen (PLoS ONE, 2025)
To address the issue of low accuracy caused by multipath effects in BeiDou satellite-based slope monitoring, this study proposes a multipath error mitigation technique based on the BeiDou Navigation Satellite System (BDS). By introducing a real-time error correction mechanism, the proposed method significantly reduces the impact of multipath effects on positioning accuracy and deformation monitoring precision. The research methodology comprises multipath effect analysis and modeling, a real-time error correction mechanism based on correction signals, and further enhancement of accuracy and stability through the integration of Kalman filtering and multi-source data fusion optimization techniques. Experiments conducted under various environmental conditions validate the effectiveness of the proposed multipath error mitigation approach. The results demonstrate that in complex terrains such as mountainous areas and canyons, the positioning accuracy improved by 53.53% to 66.40% after applying correction signals, while the deformation monitoring accuracy increased by 50.62% to 60.10%. Furthermore, through multi-source data fusion optimization, the improved positioning accuracy reached a 71.16% enhancement, and deformation monitoring accuracy was improved by 66.84%. The experimental findings strongly confirm the significant advantages of the real-time error correction technique based on the BeiDou system in improving the accuracy of deformation monitoring.